Comparative genomics of dairy-associated Staphylococcus aureus from selected sub-Saharan African regions reveals milk as reservoir for human-and animal-derived strains and identifies a putative animal-related clade with presumptive novel siderophore - Jans, Christoph; Wambui, Joseph; Stevens, Marc J. A.; Tasara, Taurai (Frontiers in Microbiology, 2022)
Staphylococcus aureus infection is considered to be a neglected tropical disease with huge impact on human and animal health alike. Dairy production in sub-Saharan Africa (SSA) relies heavily on various animals such as cows, goats and camels, depending on the region. S. aureus causes mastitis and exhibits high prevalence in raw milk. The population structure including genotypic and phenotypic traits of dairy S. aureus in relation to animal and human isolates is, however unknown for SSA. In this work, 20 S. aureus dairy isolates from East and West Africa were selected for comparative genomics and phenotypic analysis. Comparing their population structure revealed a large diversity of different origins suggesting milk to be a reservoir for human and animal strains alike. Furthermore, a novel putative siderophore was detected in multiple strains in a distinct animal-clade with strains of global origin. This putative siderophore shares a high genetic identity with that from Streptococcus equi suggesting possible horizontal gene transfer. These findings combined with the virulence genes harbored by these dairy-derived strains such as pvl, human evasion factor scn various enterotoxin, leucocidin and antibiotic resistance genes, stresses the need for an integrative One Health approach to tackle the problem of S. aureus infections in animals and humans in sub-Saharan Africa.